Banking Management System – Logistic 2 (Vendor Portal, Vehicle Reservation, Document Tracking, Audit Management): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Logistics II process involves scheduling a vehicle, assessing its capacity, tracking documents, providing web-based services for vendors, and recording and reporting the movement of raw materials from the warehouse to ensure optimal satisfaction for the company. Logistics analysis involves using documents, worksheets, and reports, including performance checklists and scorecards, to provide an overview of how specific areas of the logistics system are performing. The Banking and Finance Management System Logistics II is more useful with well-organized records and regular tracking of transactions during logistics.To avoid technological obstacles, Agile is the most effective strategy. Our Agile development methods, including bulk orders, continuous deployment, build deployment, and test automation, reduce the risk of rework and minimize the time needed to complete the process.